Impact of Royal Jelly on Infertility: A Review - Chalapathy, Chethana V.; Chatterjee, Architha; Jayaramaiah, Uday; Shivasharanappa, Kirankumar; Hanchinalmath, Jayashree V.; Patil, Sharangouda J. (Asian Journal of Biological and Life Sciences, 2020)
Royal Jelly (RJ) is most wanted healthy food supplement that makes lots of health benefits. One of the benefits include that it can act as potent supplement for healthy egg to help women with infertility. This review is focused on the recent developments in use of RJ in the treatment of infertility and boon for them to give a dream child. The healthy egg is very phenomenal key factor for the in vitro fertilization to be successful in sexing with sperm. RJ is traditionally used as health supplement for infertility treatment from the ancient time in Indian traditional system. The recent literature revealed that, scientific and traditional findings are proven it RJ is one of the therapeutic molecule and act as a food supplements that can be used it in to improve egg cell physiology. Although, there is no clinical research studies have been reported yet on RJ. Hence, in this review explored the comprehensive report on health benefits of RJ and its impact on reproductive aspects in particular in egg development of women during ovulation. This article will be the key step to the researchers and scientists who are involved in searching alternative, cost effective and without side effect for treating infertility in global scenario.
Keywords: Cell; Clinical; Egg; Fertilization; Health; Infertility; Royal Jelly; Sperm